ORBITING A SCIENCE PROGRAM. - Lansdown, Brenda (Science Education, 1962)
The article presents information on a method to drive elementary school children into making science discoveries as well as to push elementary school teachers into a science program. Under this method, it has been assumed that all school children are able to make discoveries about scientific phenomena if provided with suitable materials. Students are free to discuss about their discoveries with each other. Different sets of materials are placed on tables or desks, so that about four children can access one table. The best way to appreciate the results of this procedure is to listen to some of the conversations among the students regarding their discoveries. Student teachers are required to keep an account of these discussions. It is essential that the children must articulate their discoveries in their own words. This can be made evident from the repetition of a child's idea by the other, but using a different phrase. The final act of this procedure is to dictate a group statement of the discoveries. At this stage, a teacher should not convey her phrases or the platitudes from a textbook. On the contrary, she must allow the children to describe their discoveries in their own words, which they have discussed among each other.